Ginčai ir jų sprendimas XV amžiaus Lietuvoje: apgautų pirklių bei nusikaltusių kunigų pavyzdžiai - Rowell, Stephen C. (Lietuvos istorijos studijos, 2007)
This article examines briefly the resolution of conflicts within two separate mediaeval social groups, namely the merchant communities of Gdansk, Vilnius and Kaunas during the first seven years of Casimir l and IV's reign in the Grand Duchy of Lithuania, and the Roman Catholic clergy of the dioceses of Vilnius and Žemaitija involved in criminal cases reviewed by the Papal Curia. Attention is paid to the importance of social concepts such as friendship and charity, and the restoration of good repute. This article forms part of a broader study of Lithuania during the reign of Casimir Jagiellonczyk.